Growth of Long pepper (Piper rectofractum Vahl.) with Different Growing Media Composition - Wuri Prameswari; Welly Herman; Umi Salamah (PendIPA Journal of Science Education, 2021)
Long pepper (Piper retrofractum Vahl.) It is one of the potential medicinal plants in Indonesia. However, information related to the cultivation of this plant is still minimal. Therefore, research needs regarding the determination of suitable planting media for the growth of herbal chilies. This experiment used a complete randomized group design (RKLT) with one treatment factor for the composition of the growing media, namely soil, soil + sand (3: 1, v / v), soil + rice husk charcoal (3: 1, v/v), and soil + manure (3: 1, v / v). Each treatment repeats six times, and each consisted of 10 plants. Data analysis using a variance. The plant material used was in soil tendrils and polybags measuring 30 cm x 30 cm as a container. NPK + Mg inorganic fertilizer with an equivalent dose of 12: 12: 17: 2. The results of the experiment showed that the composition of the different growing media affected all observed variables. The use of soil planting medium + cow manure showed the best growth results of chili herbs for plant height, the number of leaves, root length, root and canopy wet weight, and root and canopy dry weight.